Design of and Experiment on Reciprocating Inter-Row Weeding Machine for Strip-Seeded Rice - Yu Wang; Xiaobo Xi; Meng Chen; Yangjie Shi; Yifu Zhang; Baofeng Zhang; Jiwei Qu; Ruihong Zhang (Agriculture, 2022)
To solve the problems of high labor costs, a low weeding rate and a high seedling injury rate in the direct seeding of rice fields, this paper presents a reciprocating inter-row weeding machine for strip-seeded rice. The machine uses a combination of weeding wheels and weeding shovels to improve the efficiency of weeding between rice rows. Its reciprocating mechanism was designed and optimized. The simulation model of weeding teeth–paddy soil interaction was established in EDEM. The structural parameters of the weeding teeth were optimized, and the bending angle of the optimized weeding teeth was 55°. A prototype trial production and field tests were carried out. The results showed that the prototype’s inter-row weeding rate was between 80.2% and 85.3% and the seedling injury rate was between 3.5% and 5.1% when the prototype’s working speed was 1~3 km h−1. The faster the speed of the prototype, the lower the inter-row weeding rate and the higher the seedling injury rate.